National Health Service : deputation to Minister of Health on 17 June 1946 (report) - Bevan, Aneurin, 1897-1960
1946-06-25 1946 1940s 9 pages -11- MR. ALLEN finally thanked the Minister for the very great trouble he had taken in dealing with the points raised by the deputation. The Minister could rest assured that so far as the T.U.C. were concerned and the bodies associated with it, they would give their moral support to the new measure, in the hope that it would have a reasonably satisfactory passage through the House. MR. BEVAN said that he appreciated the assistance of the T.U.C. and the importance of that assistance. He did not think that there was disagreement on any fundamental issues. THE DEPUTATION THEN WITHDREW. CRD.EM.DAP. 25.6.46. 292/847/4/113